Answer:
h = g t₂ t₁ - t₁²
Step-by-step explanation:
given,
At t = 0 s the rock is at ground level
At t = t₁ rock reaches at the height of the tower
Assuming height of tower be h
At t = t₂ rock is at the highest point.
distance of the tower = speed × time
at the highest point velocity is zero
using the kinematic equation
v = u +a t
![0 = (h)/(t_1)-g(t_2-t_1)](https://img.qammunity.org/2020/formulas/physics/high-school/jcrzpmnzz2559xslezy7t58xs5lpnlylof.png)
![h = t_1 ( g(t_2-t_1))](https://img.qammunity.org/2020/formulas/physics/high-school/ron7e7yyt96juyv23zbebcj0pvi4sogtri.png)
h = g t₂ t₁ - t₁²